The diagnosis of severe obsessions in the setting of kratom withdrawal and treatment with lorazepam: Case report. Issue 1 (1st December 2020) - Sablaban, Ibrahim M.; Gautam, Mohan
Abstract: Commercially available Kratom ( Mitragyna speciosa ) is a dietary supplement that has gained popularity in the United States for its psychoactive effects and potential medicative properties as an opioid receptor agonist. Likewise, sudden discontinuation may be accompanied by an opioid-like withdrawal. We present the first case in the literature of the withdrawal manifesting in disturbing obsessive thoughts after the substance was used as an opioid replacement treatment by our patient, as well as the first case where lorazepam is utilized for mitigation of these thoughts.